Effect of gold nanoparticles (AuNPs) on isolated rat tracheal segments - Maldonado-Ortega, Daniel Alberto (Toxicol Rep, 2021)
The AuNPs have been used in biomedicine as therapeutic tools for cancer. However, its role in the context of respiratory physiology has been little studied. This study aimed to determine the impact of AuNPs on respiratory smooth muscle tone, using a model of isolated tracheal rings from female and male rats precontracted with acetylcholine (ACh). AuNPs exerted a contractile effect only in the concentration of 100 ug/ml. This contractile effect was not modified by gender. The possible mediator (+)could be nitric oxide (NO), measured in a physiological solution containing the tracheal rings treated with different concentrations of AuNPs. The results obtained in this study show that the AuNPs are bio-inert in a concentration range of 0.1−10 μg/mL; however, 100 μg/mL could trigger airway hyperresponsiveness. Similar effects were obtained in isolated trachea rings treated with 100 μg/mL HAuCl4. An evaluation of HAuCl4 in physiological buffer at various HEPES concentrations (0–20 mM) showed the formation of AuNPs that could explain the contractile effect on the tracheal smooth muscle.